2018
DOI: 10.1016/j.jtcvs.2018.08.081
|View full text |Cite
|
Sign up to set email alerts
|

Reduced proximal aortic compliance and elevated wall shear stress after early repair of tetralogy of Fallot

Abstract: Objective: Patients with tetralogy of Fallot are at risk for late aortic complications due to progressive aortic root dilation and decreased aortic compliance. Early repair normalizes aortic dimensions by preadolescence. It is not known if early repair normalizes aortic wall histology and compliance or reduces late aortic complications. We used 4-dimensional flow magnetic resonance imaging to determine if children with tetralogy of Fallot repaired in infancy had normal aortic dimensions and to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…5,6 Aortopathy has been demonstrated by our group and others to be present within defined congenital heart disease pathologies, most notably conotruncal anomalies. 1,7,8 Proposed mechanisms for abnormal aortic biomechanical and structural properties include increased flow jet angles and resultant flow eccentricity. 9 Magnetic resonance imaging (MRI) has emerged as a preferred strategy for determining cardiovascular anatomy, blood flow velocities and volumes, regional and global ventricular function, and myocardial health.…”
mentioning
confidence: 99%
“…5,6 Aortopathy has been demonstrated by our group and others to be present within defined congenital heart disease pathologies, most notably conotruncal anomalies. 1,7,8 Proposed mechanisms for abnormal aortic biomechanical and structural properties include increased flow jet angles and resultant flow eccentricity. 9 Magnetic resonance imaging (MRI) has emerged as a preferred strategy for determining cardiovascular anatomy, blood flow velocities and volumes, regional and global ventricular function, and myocardial health.…”
mentioning
confidence: 99%
“…Patients with congenital heart disease including CTA may present with dilatation of the thoracic aorta during their lifetime. Histological abnormalities of the aortic wall have been identified in patients with ToF and d-TGA as responsible for the early presentation of aorta dilation despite early surgical repair (10,12,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Wave intensity defined as dI (A) = dUdlnA differs from the definition of wave intensity dI (P) = dPdU by a difference in dimensions [wave intensity dI (P) has the units W/m 2 and dI (A) has the units m/s] (14,15). However, it can be shown that they differ only by a scaling factor, ρc 2 , where ρ = blood density (16).…”
Section: Wave Intensity Analysismentioning
confidence: 99%
“…With this novel and innovative study, Schafer and colleagues 1 have turned a spotlight on the overlooked (presumptively healthy) left side of the heart in repaired tetralogy of Fallot (TOF). Although emphasis has been paid to the management of the right ventricular outflow tract in TOF, this report calls attention to the potentially hostile nature of the aorta in this disease.…”
Section: Joseph B Clark MDmentioning
confidence: 99%